PERILAKU PENCARIAN PELAYANAN KESEHATAN PESERTA JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) DI KOTA GORONTALO - , Nelson E. Panu; , Dr. drg. Julita Hendrartini, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Average utilization of Jamkesmas inpatients at health centers throughout Gorontalo Municipality 2007-2008 was still below the national target (15%). The result of preliminary survey at Pilolodoa Health Center of Gorontalo Municipality in January â July 2008 showed that only 38.03% of Jamkesmas participants used health service. This data indicates that 61% Jamkesmas participant that don't utilize health service at secondary health center and health centers. despite availability and accessibility of health staff and facilities, Jamkesmas participant do not utilize health service at secondary health center and health centers. Objective: To get an overview of health service seeking behavior of Jamkesmas participants at Gorontalo Municipality. Method: The study was qualitative with phenomenology design. Informant consisted of 40 people comprising of 31 Jamkesmas participants, 1 head of Gorontalo Municipal Health Office, 2 heads of health center, 2 heads of village, 2 heads of community empowerment institution in the village and 2 health cadres. Data were obtained through focus group discussion with Jamkesmas participants